Pemanfaatan Kotoran Ayam untuk Peningkatan Kualitas Pucuk Tebu Sebagai Pakan Ruminasia - C I Sutrisno; B.W.H.E Prasetyono; E Ali (Caraka Tani: Journal of Sustainable Agriculture, 2006)
Experiment was carried out in two stages. The first was aimed to study the viabilty of microbe of dried-oven manure and dried-sunshine manure. Completely Randomized Design (CDR), 3 treatments and 4 replications, was used throughout the experiment with content of manure microbe as the parameters. The research result indicates that the way of draining degraded the viability of microbia manure. Manure microbia’s viability of dried-oven manure was better than that of the dried-sunshine manure.The second was aimed to investigate the effect of dried-manure as starter with different time of fermentation on the quality of fermented sugar cane. Completely Randomized Design, factorial pattern 3x3 by 3 replications was employed during the experiment. The first factor was starter levels (A): 0, 15 and 30%, while the second was different time of fermentation (W): 0, 4 dan 8 week. Parameter perceived by fermented fiber component, which analysis by Analysis of Variance, while the differences among the treatment were tested with the Duncan Multiple Range Test (DMRT), continued by Polinomial Ortogonal. Fermented sugar cane by dry manure with different time of fermentation degraded the rate of NDF and ADF. The best performance was reached at 30% of starter and 4 weeks of fermentation.